TECHNOLOGY OF DEODORIZATION OF SOYABEAN OIL - D. J. Hujakulova; Sh. M. Ulashov; D. K. Gulomova (Galaxy International Interdisciplinary Research Journal, 2021)
The technology of deodorization of local soybean oil has been studied. Soybean oil is obtained from soybean seeds grown locally. For deodorization, oils were obtained under production conditions. Studies conducted in laboratory and production conditions. The effect of pressure, temperature and duration of the deodorization process on the quality indicators of deodorized oil has been studied. Equipment and technological lines for the deodorization of local varieties of soybean oil have been selected. Research in production tests carried out on a bubbling device consisting of tubes with holes for bubbling steam into oil. To maintain absolute pressure during deodorization, steam ejector vacuum systems were used. The effectiveness of such systems on soybean oil ranged from 75 to 95%. Distillates deodorization ranged from 0.25 to 0.50% of the raw materials supplied to the deodorizer. In experiments, tocopherols and sterols were isolated from the distillate and fatty residue of water from a barometric condenser. The use of tocopherols as food antioxidants was carried out by comparison with other food and synthetic products. The results obtained ensured an increase in the quality and perfection of the technological processes of deodorization of soybean oil.